Julian Amery: Navigating Britain’s Shift from Imperialism to European Integration, 1950-1970 (Global Journal of Human-Social Science, 2024)
By examining the early political career of the Conservative MP Julian Amery this article considers how the British government attempted to restore its international influence Using Amery s career as a lens this article explores the international context which enforced his change in political leanings shifting away from neo-colonial imperialism towards Europeanism It will build upon existing literature notably Sue Onslow and Lucia Bonfreschi s contribution on Amery s career and go against a recent trend of examining the legacies of Powellite politicians In doing so it examines three key themes Firstly it investigates the role of the Mau Mau rebellions in fostering a more radical role as an advocate for sustaining British imperial controls abroad While Amery offered no solution to the rebellion the Kikuyu attacks laid bare the weakening of the United Kingdom s overseas influence In turn Amery became one of Prime Minister Eden s most prominent critics during the Suez Crisis The Anglo-French Agreement of 1954 was viewed as another act of British appeasement towards emerging nationalist governments which ultimately damaged the United Kingdom s international reputation Furthermore this article takes into account the shift from conventional to nuclear defence policies following Soviet Premier Nikolai Bulganin s threat of atomic weapon attacks during the Suez Crisis and how Amery tried to shape British nuclearization as a means of maintaining the United Kingdom s influence abroad And finally this article examines Amery s legacy in institutionalizing Franco-British cooperation over aeronautical technologies in the civil and military aviation fields since joint projects like the SEPECAT Jaguar and Concorde afforded the United Kingdom the platform on which to enter the European Communities
Keywords: neo-colonial imperialism; european integration; suez group; Europeanism